A constituição e a cobrança da contribuição social incidente sobre a folha de salários e demais rendimentos do trabalho na Justiça do Trabalho - Mortari, Edson Franciscato (2015)
Commonly speaking, constitution of tax credit undertakes application of the general rule, abstract to the phenomenon event, characterized by a positive movement, which constitutes facts and tax-legal obligations solely exercised by the Executive Branch (assessment) and by the tax payer (tax return and payment). However, with enactment of Constitutional Amendment 20/98, this rule was altered upon the Judiciary Branch being granted jurisdiction, specifically Labor Justice, to constitute tax credits related to the social contributions set forth in article 195, I, a and II of the Federal Constitution. This new form of tax credit constitution is not envisaged in the National Tax Code, which sets that the act of constitution tax credit trough assessment is not related to administrative authority, which creates a gap in the constitution rules in force triggering possible distinct normative treatments for equal taxes. As a consequence, some matters related to the nature of the constitution of tax credit by the Labor Justice and the applicability of the prescription (time barring) rules will be analyzed in this study so the tax-legal relations created and demanded in labor claims are not treated with less respect in compared to substantive law, thus avoiding mistakes and maintaining safety and predictability, which are inherent to the legal system